Sustainable Farming for the Future: A Conceptual Framework for Integrating Smart Technologies and Sustainability in Small-Scale Agriculture - Ahmad Pozin, Mohd Affendi; Syed Idrus, Syed Zulkarnain; Nor Johari, Atikah; Shelena Soosay Nathan, (Journal of Technology Management and Business, 2026)
Smallholder farmers remain the backbone of the global food system, contributing substantially to food security, rural employment, and economic development. However, they face increasing challenges arising from climate change, resource scarcity, environmental degradation, and socio-economic constraints. Recent advancements in Information and Communication Technologies (ICT), including the Internet of Things (IoT), artificial intelligence (AI), unmanned aerial vehicles (UAVs), decision support systems (DSS), and blockchain, have introduced new opportunities for transforming traditional agriculture into smart and sustainable farming systems. This literature review integrates two major perspectives—smart farming and sustainable agriculture—into a unified conceptual framework. Drawing upon recent scholarly literature, the review examines how high-tech tools enhance productivity, environmental stewardship, social empowerment, and governance transparency, particularly within small-scale farming systems. Furthermore, the paper highlights key barriers to technology adoption and outlines future research directions. The findings demonstrate that the integration of digital technologies into smallholder agriculture holds significant potential to enhance resilience, sustainability, and long-term food security.